2011
DOI: 10.1039/c1jm11077b
|View full text |Cite
|
Sign up to set email alerts
|

Growth mechanism of Ni0.3Mn0.7CO3 precursor for high capacity Li-ion battery cathodes

Abstract: Co-precipitation is a promising method for the synthesis of precursors for lithium ion battery cathodes because it leads to homogeneous composition, narrow particle size distribution, and high packing density materials. Carbonate coprecipitation, as a process to produce transition metal (Mn, Ni, Co) precursors, [1][2][3] has many advantages compared to hydroxide process: First, in the carbonate matrix, the oxidation state of the cations is kept as 2 for all transition metals. Second, the experimental condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
120
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(120 citation statements)
references
References 31 publications
0
120
0
Order By: Relevance
“…(Co 0.5 Mn 0.5 )CO 3 is prepared beforehand by mixing a solution of cobalt and manganese sulfate with ammonium bicarbonate solution. In addition, Ni x Mn 1−x CO 3 can be prepared from nickel and manganese sulfate, sodium carbonate, and ammonium hydroxide (Lee et al, 2006;Ito et al, 2008;Koenig et al, 2011;Wang et al, 2011). Another transition metal precursor is NiMnO 3 , which can be prepared by heating nickel manganese double hydroxides at 600°C for 4 h, then NiMnO 3 is mixed with lithium hydroxide for the subsequent solid-state reactions (Ohzuku et al, 2011).…”
Section: Solid-state Reaction In Combination With Co-precipitationmentioning
confidence: 99%
See 1 more Smart Citation
“…(Co 0.5 Mn 0.5 )CO 3 is prepared beforehand by mixing a solution of cobalt and manganese sulfate with ammonium bicarbonate solution. In addition, Ni x Mn 1−x CO 3 can be prepared from nickel and manganese sulfate, sodium carbonate, and ammonium hydroxide (Lee et al, 2006;Ito et al, 2008;Koenig et al, 2011;Wang et al, 2011). Another transition metal precursor is NiMnO 3 , which can be prepared by heating nickel manganese double hydroxides at 600°C for 4 h, then NiMnO 3 is mixed with lithium hydroxide for the subsequent solid-state reactions (Ohzuku et al, 2011).…”
Section: Solid-state Reaction In Combination With Co-precipitationmentioning
confidence: 99%
“…Since reactions are controlled by solid-state diffusion, time, and energy consumption are important factors. For preparation of xLi 2 MnO 3 ·(1 − x)LiMO 2 (M = Ni, Co, Mn), the precursors consist of transition metal salts (acetates of Ni 2+ , Co 2+ , Mn 2+ ) (Wang et al, 2012;Yu and Zhou, 2012;Yu et al, 2012aYu et al, ,b, 2013a, manganese-nickel-cobalt hydroxides (Kim et al, 2002(Kim et al, , 2004Johnson et al, 2007;Li et al, 2011;Xu et al, 2011;, or carbonates (Deng et al, 2010;Croy et al, 2011;Koenig et al, 2011;Wang et al, 2011), and a lithium-containing compound (usually lithium hydroxide). The stoichiometric mixture is initially decomposed at 480-600°C for 3-15 h, then pelletized and calcined at 850-1000°C for 10-24 h in air.…”
Section: Solid-state Synthesismentioning
confidence: 99%
“…Many studies have shown that the electrochemical performance of the final product strongly depends on the properties of the precursor, such as morphology [10][11][12][13], size of the primary and secondary particles [13][14][15][16], size distribution [17], composition [6,8,9,[18][19][20][21], as well as structure [22,23]. Therefore, it is vital to control the precursor in order to obtain the materials with excellent performance, for which a simple and controlled preparation method is highly required.…”
Section: Introductionmentioning
confidence: 99%
“…Aiming at these problems, researchers usually use a simultaneous dripping method with a chelating agent. The dripping process is always very slow, during which controlling the synthesis condition strictly is still a difficult and tedious task [4,17,37]. The hydrothermal method could also prepare NiCoMn precursors at micron size, but it is difficult to control the morphology of particles and the starting materials are relatively expensive [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…While this study suggests that predictive calculations should be done to adjust the feed stoichiometry to target the desired precipitate stoichiometry, this is rarely reported. Of the 150 co-precipitation papers cited from the recent literature above, only 6 performed equilibrium calculations as part of their analysis 68,[81][82][83][84][85] , none used this analysis to guide their feed conditions, only some confirmed the stoichiometry of the transition metals in the precipitate 68,71,73,74,[86][87][88][89][89][90][91][92][93][94][95] , and none considered whether the relative rate of co-precipitation was different for the different transition metals. In this paper, we will use equilibrium calculations to guide the selection of feed conditions to achieve precursors with explicit composition control and will demonstrate the importance of such control for some solution conditions and impact on the electrochemical behavior of an exemplar cathode material.…”
Section: Introductionmentioning
confidence: 99%